EFFECT OF INCREASING INVESTMENT ATTRACTIVENESS IN SMALL INDUSTRIAL ZONES ON INVESTMENT ACTIVITY - Mannapova Shakhnoza Elshodovna (Web of Journals Publishing, 2025)
The article is based on the scientific research of the essence and regulatory legal bases of investment activity, revealing the conditions and factors of increasing investment activity in small industrial zones, studying the foreign experiences of increasing investment activity in small industrial zones and considering the possibilities of use.
Keywords: Small industrial zones, investment program, investment project, investment activity, consulting, emission, investment potential, investment environment, investment resource.